Climate’s firm grip on glacier ablation in the Cordillera Darwin Icefield, Tierra del Fuego - Franziska Temme; Christian Sommer; Marius Schaefer; Ricardo Jaña; Jorge Arigony-Neto; Inti Gonzalez; Eñaut Izagirre; Ricardo Giesecke; Dieter Tetzner; Johannes J. Fürst (Nature Communications)
Abstract The Cordillera Darwin Icefield (CDI) in Tierra del Fuego is one of the largest temperate ice bodies in the Southern Hemisphere. We simulate the climatic energy and mass balance of its glaciers (2000–2023), which are sensitive indicators of climatic changes in the Southern Hemisphere’s higher mid-latitudes. Year-round westerly winds cause strong climatic gradients across the mountain range, reflected in the energy and mass fluxes. Our results reveal a significant increase in surface melt (+0.18 m w.e. yr-1 per decade) over the past two decades. We also present the first estimate of dynamically controlled mass loss into adjacent fjords and lakes by frontal ablation, amounting to 1.44 ± 0.94 Gt yr-1 (26 % of the total CDI mass loss). Frontal losses are mainly channelized through few marine-terminating glaciers. While frontal ablation is important for predicting the fate of individual glaciers, for the CDI as a whole, atmospheric conditions exert the main control on the current glacier evolution.